The image of Belinsky in public consciousness at the turn of the 20th century - Крылов, Вячеслав (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The article is devoted to chosen aspects of myth formation about Belinsky in the Russian culture at the turn of the 20th century. The analysis is done on the basis of journal and newspaper criticism and essays, fiction and theoretical discussions about Belinsky.